Penciptaan Batik Tulis Motif Jangka Kala dan Aplikasi Makrame pada Ready to Wear Deluxe - Grantiana, Stella Aurelia; Suharno, Suharno; Marlianti, Mira (Style : Journal of Fashion Design, 2024)
The creation of this work is based on two things. First, the author's desire to remind the importance of time for mankind. This is important because everything has its time, and most people do not succeed because they do not make the best use of their time. Secondly, there is no ready to wear deluxe (rtw-deluxe) that applies batik tulis motifs of the “Jangka Kala” (time) and makrame. Therefore, the purpose of this creation is to enrich the form of rtw-deluxe that can function as a media to remind the importance of time in human life. The form of the work refers to Resilent, namely Heritage with the sub-theme Reminiscene Rtw-deluxe was chosen because it has an exclusive, classy impression and is able to accommodate the creative ideas of the author. The method of creation used is exploration, design, and realization. The results of this creation are in the form of 4 batik jam motifs applied to ready to wear deluxe and presented in the form of a fashion show at the Jakarta Muslim Fashion Week entitled Nea Gennisi.